Organizações não governamentais no campo educacional: um estudo exploratorio - Silva, Gerson Aparecido Cordeiro da (2010)
The project sought to verify the extent to which external influences change the pedagogical project of the researched NGOs and how they put into practice their actions to educate their target audience. Our central question is whether the NGOs maintain a character of social movement, seeking or not through this to improve the life of the community in which it operates. This question puts the researcher the requirement to divide the NGOs into Community and Business. (AU)